Adequacy of pain management in oncology patients at a tertiary hospital in Ghana - Abruquah, Akua A.; Biney, Robert P.; Osei-Bonsu, Ernest B.; Boamah, Kofi M.; Woode, Eric (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Although cancer pain is well documented, efficient management is largely inadequate in most patients especially in developing countries. This study evaluated the adequacy of pain management as well as potential social factors that may be associated with inadequate pain management. Methods: 204 ambulatory oncology patients (82% female; mean age 53.5) attending clinic at the Oncology Directorate, of a tertiary hospital in Ghana from January to December, 2015 were recruited and their pain severity and functional interference assessed with the Brief Pain Inventory (BPI). The adequacy of pain management was computed as the pain management index (PMI) using the BPI. Results: Although 62% of respondents were prescribed high potency opioids, 56.9% of them exhibited significant pain while 34.9% required a stronger analgesic to manage their pain. Majority of patients (56%) were over-managed for their pain (had PMI score >0). Only 26.4% had optimal cancer pain management. Pain interfered mostly with patients’ sleep (46.2%) and general activity (42.5%). Patients with high pain intensity were more likely to have it affect their daily activity (P<0.0001). Men were more likely to have inadequate pain management than females. Conclusions: This study has shown that whereas pain management may be adequate, there is the tendency for opioid tolerance and abuse as over 50% of patients receive more analgesics than required. The tenets of the WHO 3-step analgesic ladder should be strictly adhered to achieve optimum cancer pain relief.